2016
DOI: 10.3109/15376516.2016.1163448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electronic-cigarette refill liquid on rat testis

Abstract: Electronic cigarettes (e-cigarettes) are becoming the fashionable alternative to decrease tobacco smoking, although their impact on health has not been fully assessed yet. The present study was designed to compare the impact of e-cigarette refill liquid (e-liquid) without nicotine to e-liquid with nicotine on rat testis. For this purpose, e-liquid with nicotine and e-liquid without nicotine (0.5 mg/kg of body weight) were administered to adult male Wistar rats via the intraperitoneally route during four weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 42 publications
6
38
0
1
Order By: Relevance
“…It has been well documented that tobacco cigarettes are toxic to airway cells (Wu and Lee 1985;Matsumoto et al 1998;Wright et al 1999); however, we have described that at lower concentrations, they do not provide a toxic effect to macrophages, but rather affects their function. Whilst E-cigarettes are a relatively new product on the market, many papers now show that they too have toxic effects on a range of cells (Bahl et al 2012;McGrath-Morrow et al 2015;El Golli et al 2016;Sancilio et al 2016;Sherwood and Boitano 2016;Welz et al 2016) including airway epithelial cells (Scheffler et al 2015;Schweitzer et al 2015). This effect is non-nicotine dependent, and there has been particular interest in certain flavors including tobacco, cherry, and cinnamon, that have been shown to be more toxic than others (Bahl et al 2012;Behar et al 2014;Kosmider et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that tobacco cigarettes are toxic to airway cells (Wu and Lee 1985;Matsumoto et al 1998;Wright et al 1999); however, we have described that at lower concentrations, they do not provide a toxic effect to macrophages, but rather affects their function. Whilst E-cigarettes are a relatively new product on the market, many papers now show that they too have toxic effects on a range of cells (Bahl et al 2012;McGrath-Morrow et al 2015;El Golli et al 2016;Sancilio et al 2016;Sherwood and Boitano 2016;Welz et al 2016) including airway epithelial cells (Scheffler et al 2015;Schweitzer et al 2015). This effect is non-nicotine dependent, and there has been particular interest in certain flavors including tobacco, cherry, and cinnamon, that have been shown to be more toxic than others (Bahl et al 2012;Behar et al 2014;Kosmider et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of data on e-cigarette and e-liquid exposure. We previously showed deleterious effects of e-liquid by pointing out oxidative damages, histopathological changes and steroidogenesis disturbance in the rat testis (12). In the present study, we brought new insights about e-liquid toxicity in the rat epididymis by highlighting epididymal oxidative stress imbalance and inflammation, leading to a spermatogenesis shortage.…”
Section: Discussionmentioning
confidence: 50%
“…Nicotine is known to increase ROS by breaking down the mitochondrial respiratory chain (20) and to modify the antioxidant system (5,30). Moreover, we have previously shown that e-liquid treatment could induce a modification of oxidative status in different organs (10,11), especially in the testis causing steroidogenesis alterations (12). Thus, nicotine action could explain the obtained results of E-liquid group.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…En conjunto, los hallazgos de este estudio evidencian que la movilidad inicial de las muestras seminales se afecta por el vaporizador independiente de la concentración de nicotina (6 mg/mL o 3 mg/mL), paradójicamente a menor concentración de nicotina los efectos sobre los espermatozoides son más marcados, resultados congruentes con los reportados previamente por El Golli y col., 23 los cuales fueron los primeros en reportar que las esencias sin nicotina de los cigarrillos electrónicos aplicadas directamente en testículos de roedores, afectan la viabilidad espermática. La nicotina es conocida además por inhibir la biosíntesis de testosterona en las células de Leydig en ratones la cual juega un papel importante en la espermatogénesis por lo que reduce la producción y maduración espermática.…”
Section: Discussionunclassified